Safety of ultrasound exposure: Knowledge, attitudes and practices of Australasian sonographers. Issue 3 (14th June 2017) - Moderiano, Monique; McEvoy, Maureen; Childs, Jessie; Esterman, Adrian
Abstract: Introduction: While perceived as safe, diagnostic ultrasound has the potential to cause biological effects on the body tissues. The aim of this study was to evaluate knowledge, attitudes and practices of Australasian sonographers on bioeffects and safety of ultrasound scanning. Methods: Focus groups were used to develop a questionnaire to explore knowledge, attitudes and practices of ultrasound safety, which was then distributed to Australasian sonographers. Thematic (focus groups) and descriptive (questionnaires) analyses were undertaken. Results: A 37‐item questionnaire addressed knowledge, attitudes and practices of ultrasound safety. In 47 collected responses, sonographers demonstrated good familiarity of thermal index (TI) (79%), mechanical index (MI) (68%) and 'as low as reasonably achievable' (ALARA) principle (85%). However, most sonographers could not accurately define TI (13%) and had poor knowledge of safety guidelines relating to TI (19%) and MI (14%). Over 30% were uncertain about their attitudes to ultrasound safety issues. While 52% 'always' and 30% 'most of the time' adhere to ALARA, 37% of sonographers reported never monitoring TI and MI. Discussion: While familiar with safety terms, knowledge of safety guidelines was lacking. Many sonographers were uncertain about their attitudes to the safety of scans; and safety practices involving monitoring for bioeffects were not a high priority.